2000
DOI: 10.1007/pl00013431
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic case of X-chromosomal Alport syndrome in a consanguineous family

Abstract: Alport syndrome (AS) is a genetic disorder of basement membranes caused by mutations in type IV collagen genes that is characterized by chronic hematuria and progressive nephropathy leading to renal failure. The main extrarenal features include sensorineural hearing loss and ocular lesions. The mode of inheritance is X-linked dominant in about 80%-85% of the affected families, whereas autosomal transmission is rarely encountered. We report a male patient originating from a healthy consanguineous Lebanese famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Of the 12 biopsies obtained from children without a family history of renal disease, 8 showed grade 3 and 4 grade 2 GBM thickening. Yoshikawa et al [12,26] suggested that these may represent new mutants, as has since been confirmed in a sporadic example occurring in a consanguineous family, by the finding of a COL4A5 mutation not present in the child's mother [27]. However, in the light of the reported mutations in COL4A3 and COL4A4 genes [4], they may instead be examples of autosomal recessive inheritance.…”
Section: Discussionmentioning
confidence: 84%
“…Of the 12 biopsies obtained from children without a family history of renal disease, 8 showed grade 3 and 4 grade 2 GBM thickening. Yoshikawa et al [12,26] suggested that these may represent new mutants, as has since been confirmed in a sporadic example occurring in a consanguineous family, by the finding of a COL4A5 mutation not present in the child's mother [27]. However, in the light of the reported mutations in COL4A3 and COL4A4 genes [4], they may instead be examples of autosomal recessive inheritance.…”
Section: Discussionmentioning
confidence: 84%
“…In this case, despite some history of familial hematuria, the patient’s mutation was sporadic and not shared by either parent. Such disease-causing sporadic mutations have been characterized to occur; however, there are limited data on the frequency of such events [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%